Review: Mechanisms of TIMP-3 accumulation and pathogenesis in Sorsby fundus dystrophy - Betts, Jacob H J; Troeberg, Linda (Molecular vision, 2024)
Sorsby fundus dystrophy (SFD) is a rare, inherited form of macular degeneration caused by mutations in the gene encoding tissue inhibitor of metalloproteinases 3 (TIMP-3). There are 21 mutations currently associated with SFD, with some variants (e.g., Ser179Cys, Tyr191Cys, and Ser204Cys) having been studied much more than others. We review what is currently known about the identified SFD variants in terms of their dimerization, metalloproteinase inhibition, and impact on angiogenesis, with a focus on disparities between reports and areas requiring further study. We also explore the potential molecular mechanisms leading to the accumulation of extracellular TIMP-3 in SFD and consider how accumulated TIMP-3 causes macular damage. Recent reports have identified extraocular pathologies in a small number of SFD patients. We discuss these intriguing findings and consider the apparent discrepancy between the widespread expression of TIMP-3 and the primarily retinal manifestations of SFD. The potential benefits of novel experimental approaches (e.g., metabolomics and stem cell models) in terms of investigating SFD pathology are presented. The review thus highlights gaps in our current molecular understanding of SFD and suggests ways to support the development of novel therapies.